The Sohozky — Weierstrass theorem for entire polyanalytic functions - Balk, M. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. Б. Балк. Теорема Сохоцкого—Вейерштрасса для целых полианалитических функцийM. Balkas. Suchockio — Vejerštraso teorema sveikų polianalizinių funkcijų atveju